Brewing practices to maximise levels of catechins and other compounds with functional properties in Azorean green tea infusions: comparison with composition of canned green tea drinks - Petisca, Catarina (2009)
The influence of infusion time, temperature and water characteristics on catechins, gallic acid, theophylline and caffeine levels of Azorean green tea infusions was evaluated in two samples of green tea presenting different compositions to optimise brewing practices and maximise levels of compounds with functional properties in infusions. Additionally, the compounds under study were quantified in commercial canned green tea drinks and levels compared with composition of home-made infusions. An enhancement of epigallocatechin gallate, epigallocatechin and epicatechin gallate levels, the catechins with higher antioxidant activity, was observed as water pH decreased and infusion time increased. No correlations were found between the levels of gallic acid, theophylline and caffeine of tea infusions, and water pH. The industry of canned green tea drinks produces beverages with a composition of catechins and other bioactive compounds similar to that of home-made acidified green tea with 10-min infusion.